PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR KOGNITIF FISIKA SISWA DI SMK NEGERI 1 BANGUN PURBA KABUPATEN ROKAN HULU - Safitri, Indri; Daruwati, Ika; -, Sohibun (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
This research aimed to determine the effect of learning models make a match against physics student learning outcomes. This research was conducted in SMK 1 Bangun Purba. This type of research is true experimental design. This research design control group pre-test post-test. The population in this study a class XI student as much as 2 class with a sampling technique in this study is saturated sampling. Analysis of the data, using the N gain test, test for normality, homogeneity test and t test. The results of the t-test calculations showed that 4.740> 2.024. It can be concluded that there are significant learning model make a match against the cognitive learning physics class XI student of SMK 1 Bangun Purba with a level of 95%.